Volterra algorithm for modelling sea surface current circulation from satellite altimetry data - Marghany, Maged; Hashim, Mazlan; Cracknell, Arthur P. (Springer Berlin / Heidelberg, 2008)
This paper was utilized a new approach for modelling sea surface current from JASON-1 satellite altimetry data. This was based on utilizing of the Volterra series expansion in order to transform the time series satellite altimetry data into a real ocean surface current. Thus,the basic equation of hydrodynamic has been solved by second order Volterra model. Then, the Volterra kernel inversion used to obtain the sea surface current velocity. The finite element model of Lax-Wendorff schemes used which was based on triangular space-time elements to map the spatial current variation in the South China Sea over different monsoon periods. In situ sea surface current measurements were collected along the east coast of peninsular Malaysia by using electromagnetic current meters. The study shows that the maximum current magnitude of 1.2 m/s was occurred during the northeast monsoon period as compared to other monsoon periods. The main noticeable feature was an existence of anticlockwise eddy in the Gulf of Thailand. The results also shows a good correlation between in situ current measurements and the Volterra-Lax-Wendrof scheme with high R2 of 0.91. It can be said that Volterra-Lax-Wendrof scheme can be used as numerical scheme for modelling sea surface current from altimetry data.